Effectiveness of Some Reading Activities towards Improving the Reading Abilities of Primary School Pupils in Nigeria - Angela Chekwube, Ekoh-Nweke; Mkpa, Mkpa Agu (Asian Journal of Interdisciplinary Research, 2019)
The study sought to determine if the utilization of three reading activities in a remediation class for experimental (E) group of primary five (5) pupils who were deficient in reading would improve their reading abilities over their counterparts in the control (C) group taught the remedial lessons through the traditional teacher-centered approach. It also investigated if sex would be a significant factor in determining the performance of the treatment and control groups. Two research questions and two null hypothesis guided the study. The subjects were made up of 38 reading-deficient primary five (5) pupils randomly assigned to the two treatment groups. The data collection instrument was a researcher-made and validated reading assessment checklist, the inter-rater reliability coefficient of which yielded an index of 0.82 using the Pearson Product Moment Correlation Coefficients. The C and E group teachers received orientations on the approaches to adopt to carry out their task. Steps were taken to establish equivalence of the instructional conditions of the two groups, the only difference being the experimental treatment which consisted of the use of 3 activities: Reading chart activity, Paired reading and Command card game. After the remedial treatment experiment which lasted for three weeks of compact activities, the E and C subjects were tested with their class-appropriate reader. Results established the significant superiority of the experimental group over the control. Sex was not found to be a significant factor as no difference existed between the male and female pupils in the E and C groups.